1991
DOI: 10.1002/em.2850180104
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a method for quantitating food consumption for mutation assays in Drosophila

Abstract: Quantitation of food consumption is necessary when determining mutation responses to multiple chemical exposures in the sex-linked recessive lethal assay in Drosophila. One method proposed for quantitating food consumption by Drosophila is to measure the incorporation of 14C-leucine into the flies during the feeding period (Thompson and Reeder: Environmental Mutagenesis 10:357-365, 1987). Three sources of variation in the technique of Thompson and Reeder have been identified and characterized. First, the amoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 9 publications
1
15
1
Order By: Relevance
“…We measured the water consumption of flies fed two different concentrations (dietary restriction, DR; concentrated medium, CM) of yeast extract/sucrose (YE/S) medium by providing ad libitum water labeled with a radioactive tracer (21)(22)(23). Flies were housed in population cages containing separate food and water sources of similar surface area.…”
Section: Resultsmentioning
confidence: 99%
“…We measured the water consumption of flies fed two different concentrations (dietary restriction, DR; concentrated medium, CM) of yeast extract/sucrose (YE/S) medium by providing ad libitum water labeled with a radioactive tracer (21)(22)(23). Flies were housed in population cages containing separate food and water sources of similar surface area.…”
Section: Resultsmentioning
confidence: 99%
“…Preliminary experiments with a M/2 saccharose solution containing hydrogen peroxide (3.3%, w/v) and the indigo carmine stain (E132) showed that flies fed on it because their abdomen was colored in blue and blue fecal spots were observed: thus, flies did not die simply because they did not feed (see Thompson et al 1991 for a discussion of starvation in toxicology experiments).…”
Section: Longevity With Hydrogen Peroxidementioning
confidence: 99%
“…One di¤culty of this procedure is that the amount of ingested food is usually unknown, and that lethality associated with high doses may re£ect feeding rejection and thus starvation [8].…”
Section: Adding Antioxidants To Foodmentioning
confidence: 99%